Updated list of the diversity of mammals from Peru and a proposal for its updating - Pacheco Torres, Víctor Raúl (2021)
The most recent list of mammals in Peru, published in 2020, compiled a total of 569 species, including 82 endemic species. However, several taxonomic changes have occurred in this short time, and it makes necessary to publish an updated list of all mammalian species recorded in Peru. This new list is updated until November 2021 and includes 573 species, 223 genera, 51 families and 13 orders: Didelphimorphia (47), Paucituberculata (2), Sirenia (1), Cingulata (5), Pilosa (7), Primates (42), Lagomorpha (2), Eulipotyphla (3), Carnivora (33), Perissodactyla (2), Artiodactyla (46, including 32 cetaceans), Rodentia (194) and Chiroptera (189); of which 87 species are endemic to the country. On the other hand, the need to have valid and updated taxonomic lists for use in decision-making, leads us to propose as an optimal strategy that the Asociación de Mastozoólogos del Perú (AMP) assume the role to produce and maintain an updated list to satisfy the needs of different users, as similar organizations are doing in neighboring countries with the support of the State and NGOs.